1993
DOI: 10.1128/mcb.13.7.3882
|View full text |Cite
|
Sign up to set email alerts
|

The hexokinase gene is required for transcriptional regulation of the glucose transporter gene RAG1 in Kluyveromyces lactis.

Abstract: The R4GI gene of Kluyveromyces lactis encodes a low-affinity glucose/fructose transporter. Its transcription is induced by glucose, fructose, and several other sugars. The RAG4, RAGS, and RAG8 genes are trans-acting genes controlling the expression of the RAG) gene. We report here the characterization of one of these genes, RAG5. The nucleotide sequence of the cloned RAGS gene indicated that it encodes a protein that is homologous to hexokinases of Saccharomyces cerevisiae. ragS mutants showed no detectable he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
97
1

Year Published

1997
1997
1999
1999

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(99 citation statements)
references
References 49 publications
1
97
1
Order By: Relevance
“…AtHXKI and AIHXK2 share 82% nucleotide identity, and AtHXKI and AtHXK2 share 85% amino acid identity. Results of data base searches and sequence comparisons showed that AtHXK proteins share significant sequence identity with human (Nishi et al, 1992) and rat (Magnuson et al, 1989) GLK (34 to 35%) and yeast (Stachelek et al, 1986;Prior et al, 1993) HXKs (36 to 38%) ( Figure 2). Conserved ATP and sugar binding domains (Bork et al, 1993) were found in the deduced protein sequences of both AtHXK genes (Figure 2).…”
Section: Molecular Characterization Of the Arabidopsis Hxk-encoding Gmentioning
confidence: 99%
See 2 more Smart Citations
“…AtHXKI and AIHXK2 share 82% nucleotide identity, and AtHXKI and AtHXK2 share 85% amino acid identity. Results of data base searches and sequence comparisons showed that AtHXK proteins share significant sequence identity with human (Nishi et al, 1992) and rat (Magnuson et al, 1989) GLK (34 to 35%) and yeast (Stachelek et al, 1986;Prior et al, 1993) HXKs (36 to 38%) ( Figure 2). Conserved ATP and sugar binding domains (Bork et al, 1993) were found in the deduced protein sequences of both AtHXK genes (Figure 2).…”
Section: Molecular Characterization Of the Arabidopsis Hxk-encoding Gmentioning
confidence: 99%
“…A t h x k Z H w a n R a t Y e a m t l Y e a m t l Y e a r t 3 A t h x k l A t h x k Z H w a n R a t Y e a r t l Y e a m t Z Y e a m t 3 A comparison of predicted amino acid sequences of Arabidopsis AtHXK1 and AtHXK2, human GLK (Nishi et al, 1992), rat GLK (Magnuson et al, 1989), S. cerevisiae HXKl (Yeastl) and HXK2 (Yeast2) (Stachelek et al, 1986), and Kluyveromyces lactis RAG5 (Yeast3) (Prior et al, 1993) is shown. The ATP binding site (Bork et al, 1993) includes underlined regions 1, 2, and A, indicating the conserved phosphate 1 and 2 and adenosine interaction regions, respectively.…”
Section: Molecular Characterization Of the Arabidopsis Hxk-encoding Gmentioning
confidence: 99%
See 1 more Smart Citation
“…cerevisiae shuttle vector, pSK1, has replication origins from K. lactis (S11 fragment of pKD1) and S. cerevisiae (ori of 2 m) plasmids. This shuttle plasmid was originally constructed by Prior et al (1993) to characterize K. lactis homologous gene complementing an S. cerevisiae mutation and vice versa. Here, we constructed the shuttle secretion vector, pMI6, by inserting a mouse -amylase secretion cassette encoded by the 3·2 kb SalI-BamHI fragment of pMI5 (PGK promoter-signal sequence of the 128 kDa killer precursor--amylase-PGK terminator) into SalI/ BamHI-digested pSK1.…”
Section: Direct Comparison Of Secretion Efficiency Ofmentioning
confidence: 99%
“…This fragment was subcloned into BamHI-SalI-digested pSK1 (the K. lactis/S. cerevisiae shuttle vector; Prior et al, 1993) to construct pMI6. The yeast was transformed using the Li + -salt described by Ito et al (1983).…”
Section: Construction and Transformation Of Secretion Vectorsmentioning
confidence: 99%